Penerapan Metode Naïve Bayes Untuk Prediksi Kepuasan Pelanggan ( Studi Kasus Bengkel Win Motor ) - Bambang Hermanto; Ahmad Romadhoni (Jurnal SIGMA, 2019)
The tight competition in the workshop business makes a company engaged in service or maintenance of motorized vehicles compete to attract its customers in buying spare parts and services offered. To maintain its customers, a company must be able to understand carefully the expectations - any expectations of its customers so that the company must know the level of satisfaction of each customer. At WIN MOTOR Workshop which is located in the residential area of East Cikarang Graha, it is difficult to determine whether the customer feels satisfied or not in terms of the services provided. By using questionnaire techniques, the results of questionnaire data are obtained. Processing data using the application of naïve Bayes methods to predict customer satisfaction. Based on the data from the questionnaire that was processed using the naïve bayes method to predict customer satisfaction in the WIN MOTOR Workshop, the accuracy rate was 90.00%. After testing cases to determine customer satisfaction predictions using manual calculations and using the Rapidminer application, the same customer satisfaction predication results were obtained.. Keywords : Prediction, Naïve Bayes, Customer Satisfaction